A Random Selection Based Substitution-box Structure Dataset for Cryptology Applications - Ibrahim, Habib; Ozkaynak, Fatih (Ieee, 2021)
The cryptology science has gradually gained importance with our digitalized lives. Ensuring the security of data transmitted, processed and stored across digital channels is a major challenge. One of the frequently used components in cryptographic algorithms to ensure security is substitution-box structures. Random selection-based substitution-box structures have become increasingly important lately, especially because of their advantages to prevent side channel attacks. However, the low nonlinearity value of these designs is a problem. In this study, a dataset consisting of twenty different substitution-box structures have been publicly presented to the researchers. The fact that the proposed dataset has high nonlinearity values will allow it to be used in many practical applications in the future studies. The proposed dataset provides a contribution to the literature as it can be used both as an input dataset for the new post-processing algorithm and as a countermeasure to prevent the success of side-channel analyzes.
19th International Conference on Smart Technologies (IEEE EUROCON) -- JUL 06-08, 2021 -- Lviv, UKRAINE
Keywords: substitution box; block cipher; chaos; random selection